2012
DOI: 10.1007/s10822-012-9589-3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted study on the reaction between pyruvate and ylide in the pathway leading to lactyl–ThDP

Abstract: In this study the formation of the lactyl-thiamin diphosphate intermediate (L-ThDP) is addressed using density functional theory calculations at X3LYP/6-31++G(d,p) level of theory. The study includes potential energy surface scans, transition state search, and intrinsic reaction coordinate calculations. Reactivity is analyzed in terms of Fukui functions. The results allow to conclude that the reaction leading to the formation of L-ThDP occurs via a concerted mechanism, and during the nucleophilic attack on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The main conclusions can be summarized as follows: (1) the reaction between the intermediate HEThDP − and 2-ketobutyrate occurs via a stepwise mechanism consisting of two steps; (2) the first reaction step corresponds to the nucleophilic attack of the carbanion on the carbonylic carbon of 2-KB; this stage occurs via a concerted asynchronous mechanism, that is, the proton transfer follows the carboligation event; (3) the second reaction stage involves the product release and ylide recovery, allowing in this way to reinitiate the catalytic cycle once more; (4) two transition states are observed on the PES, the first one, TS1 corresponding to the first reaction step, has an activation barrier of about 11 kcal/mol, while the second one, TS2 corresponding to the product liberation, has an activation barrier of about 15 kcal/mol. (5) The results are in agreement with literature values [16,17] which states that the next step to the formation of the adduct is the rate controlling step among the last two stages of the AHAS catalytic cycle.…”
Section: Discussionsupporting
confidence: 90%
“…The main conclusions can be summarized as follows: (1) the reaction between the intermediate HEThDP − and 2-ketobutyrate occurs via a stepwise mechanism consisting of two steps; (2) the first reaction step corresponds to the nucleophilic attack of the carbanion on the carbonylic carbon of 2-KB; this stage occurs via a concerted asynchronous mechanism, that is, the proton transfer follows the carboligation event; (3) the second reaction stage involves the product release and ylide recovery, allowing in this way to reinitiate the catalytic cycle once more; (4) two transition states are observed on the PES, the first one, TS1 corresponding to the first reaction step, has an activation barrier of about 11 kcal/mol, while the second one, TS2 corresponding to the product liberation, has an activation barrier of about 15 kcal/mol. (5) The results are in agreement with literature values [16,17] which states that the next step to the formation of the adduct is the rate controlling step among the last two stages of the AHAS catalytic cycle.…”
Section: Discussionsupporting
confidence: 90%
“…Our strategy for further development of the amixicile scaffold is based on previous unpublished work associated with docking simulations with NTZ and its active metabolite TZ (the phenol) with the crystal structure of PFOR from D. africanus (20,21). Previous mechanistic and nuclear magnetic resonance (NMR) studies indicated that NTZ interferes with the PFOR enzymatic reaction as a competitive inhibitor of pyruvate binding to TPP (11).…”
Section: Resultsmentioning
confidence: 99%
“…7). Previous SAR studies, while largely inconclusive, provided clues to substituents that could further increase the inhibitory activity of the PFOR enzyme in whole cells (20). Electron-donating (EDG) and -withdrawing (EWG) groups were added to the benzene ring linker region of amixicile to establish a correlation between the spatial and electronic properties of the ring in the pocket and activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted methodology, called the cluster approach, has been very successful in elucidating reaction mechanisms of a wide variety of enzymes (Siegbahn and Himo, 2009 , 2011 ; Siegbahn and Blomberg, 2010 ; Blomberg et al, 2014 ; Himo, 2017 ). A number of previous theoretical studies using a variety of computational techniques have considered aspects of mechanism of a number of ThDP-dependent enzymes (Friedemann et al, 2004 ; Lie et al, 2005 ; Wang et al, 2005 ; Jaña et al, 2010 ; Topal et al, 2010 ; Xiong et al, 2010 ; Paramasivam et al, 2011 ; Alvarado et al, 2012 ; Hou et al, 2012 ; Jaña and Delgado, 2013 ; Sheng and Liu, 2013 ; Sheng et al, 2013 , 2014 ; Sánchez et al, 2014 ; Zhang et al, 2014 ; Zhu and Liu, 2014 ; Lizana et al, 2015 ; Nauton et al, 2016 ; White et al, 2016 ). Relevant results from these studies have been incorporated into the discussion of the BFDC mechanism below.…”
Section: Introductionmentioning
confidence: 99%